(3GdHOQ GdefhQ aj SjQI Gdedc GdeXaQ (B[ (3GdSdWGf Sdje GdYKeGfi (B]s - (3GdYdjei GdMfHdis; (3CHh Gdjef GdYdjej , YHO GdQMef Hf eMeO Hf YHO GdQMef GdYdjej GdMfHdj, eLjQ GdOjf CHh Gdjef,J (B928 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CYGO GdMb Edi fUGHg hegO bhGYO Gdedc GdTQja HYO GVWQGHg s
(3BNQgG (B:s
(3jfJgi CKfGA JQLeI GdceGd Hf CHj TQja s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B177s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs